2021
DOI: 10.1029/2020jd034300
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of the Maximum Vertical Velocity Converted From Total Lightning Data Through the EnSRF Method

Abstract: A total lightning data assimilation (LDA) scheme is developed at the cloud‐resolving scale in this study. The LDA scheme assimilates total lightning data through the ensemble square root filter (EnSRF) method based on the relationship between the maximum vertical velocity and the instantaneous flash rate. To verify the effect of LDA, three assimilation experiments based on a convective activity on July 6, 2019 are performed. The results show that all LDA experiments can improve the forecast. LDA improves the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…For cloud-resolving models, different methods have also been implemented. Wang et al [38] and Gan et al [39] assimilated LDA, adjusting the vertical velocity simulated by NWP based on the relationship between the frequency of lightning and cloud top height and on the relationship between cloud top height and maximum updraft [40,41]. Marchand and Fuelberg [42] used LDA to adjust the thermal field at the lower atmospheric levels to force convection.…”
Section: Introductionmentioning
confidence: 99%
“…For cloud-resolving models, different methods have also been implemented. Wang et al [38] and Gan et al [39] assimilated LDA, adjusting the vertical velocity simulated by NWP based on the relationship between the frequency of lightning and cloud top height and on the relationship between cloud top height and maximum updraft [40,41]. Marchand and Fuelberg [42] used LDA to adjust the thermal field at the lower atmospheric levels to force convection.…”
Section: Introductionmentioning
confidence: 99%
“…The initial conditions in numerical weather prediction models (NWPs) play a significant role in short‐term weather forecasting. Currently, radar observations (Gan, Yang, Xie, et al., 2021; Gao et al., 2016; Liu, Yang, Lai, et al., 2021; Liu, Yang, Xin, & Wang, 2021; Pu et al., 2009; Yang et al., 2006, 2015), lightning data (Fierro et al., 2012; Gan, Yang, Qiu, et al., 2021; Liu et al., 2020; Qie et al., 2014; Wang et al., 2014), satellite data (Pu et al., 2002), and so on, have been assimilated through various methods to improve the initial field of convective‐scale NWPs, and these studies have achieved good results in improving the hit rate of severe convective systems. However, in actual forecasting, there are often cases of spurious forecasts.…”
Section: Introductionmentioning
confidence: 99%
“…EnSRF has greater flexibility and can be used to assimilate nonlocal observations, such as column maximum vertical velocity (w max ). Gan, Yang, Qiu, et al (2021) proposed a scheme to assimilate the two-dimensional w max converted from lightning data through the EnSRF method. The results showed that assimilating two-dimensional w max could effectively improve the thermal fields, leading to a moist and warm conditions for convection to develop.…”
mentioning
confidence: 99%
“…However, there is no universal relationship between lightning and rainfall, and the relationship between lightning and rainfall is sensitive to storm location and season [17,[29][30][31]. By establishing an empirical relationship between the lightning frequency and vertical velocity, the vertical velocity proxy variable created from lightning data is assimilated into the model with the dynamic nudging and ensemble square root filter (EnSRF) methods [32,33]. The empirical relationships between vertical velocity or temperature and lightning are limited by local climate characteristics and differences in convective processes.…”
Section: Introductionmentioning
confidence: 99%